2001
DOI: 10.1074/jbc.m002276200
|View full text |Cite
|
Sign up to set email alerts
|

Topological Organization of the Hyaluronan Synthase fromStreptococcus pyogenes

Abstract: Since we first reported (DeAngelis, P. L., Papaconstantinou, J., and Weigel, P. H. (1993) J. Biol. Chem. 268, 19181-19184) the cloning of the hyaluronan (HA) synthase from Streptococcus pyogenes (spHAS), numerous membrane-bound HA synthases have been discovered in both prokaryotes and eukaryotes. The HASs are unique among enzymes studied to date because they mediate 6 -7 discrete functions in order to assemble a polysaccharide containing hetero-disaccharide units and simultaneously effect translocation of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
95
0
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 88 publications
(100 citation statements)
references
References 68 publications
4
95
0
1
Order By: Relevance
“…Schematic organization and alignment of class I HA synthase proteins. A: The streptococcal, vertebrate, and viral HASs are integral membrane proteins that have a similar predicted overall organization (the streptococcal enzyme is shown here because topological organization data has been obtained (Heldermon et al, 2001). A central conserved region of the enzymes is predicted to contain a catalytic domain that resides in the cytosol (Cyto); this region is used in the alignment in panel B.…”
Section: Evolution Of Gag Synthases Of Bacterial Pathogensmentioning
confidence: 99%
“…Schematic organization and alignment of class I HA synthase proteins. A: The streptococcal, vertebrate, and viral HASs are integral membrane proteins that have a similar predicted overall organization (the streptococcal enzyme is shown here because topological organization data has been obtained (Heldermon et al, 2001). A central conserved region of the enzymes is predicted to contain a catalytic domain that resides in the cytosol (Cyto); this region is used in the alignment in panel B.…”
Section: Evolution Of Gag Synthases Of Bacterial Pathogensmentioning
confidence: 99%
“…The location of the active sites of spHAS was examined experimentally and confirmed to be intracellular (29). This finding Yes for HA translocation makes sense, since the nucleotide-sugar substrates are produced in the cytoplasm.…”
Section: Mechanism Of Ha Biosynthesis By the Class I Streptococcal Hamentioning
confidence: 99%
“…The upper portion of each cartoon represents the outside of the cell membrane (indicated by the parallel lines) and the lower portion is in the cytoplasm. Only the topology of the spHAS has been determined experimentally (29). The topological organization of the seHAS and suHAS are assumed to be the same because their amino acid sequences are >70% identical to spHAS.…”
Section: Mechanism Of Ha Biosynthesis By the Class I Streptococcal Hamentioning
confidence: 99%
“…reported that the major catalytic regions of eukaryotic HAS seem to exist in the cytoplasmic region by topology research and Kyte-Doolittle hydropathy analysis (5,15,30), although the essential structure of the catalytic domain is still putative and has not been identified previously. In this study, we designed three constructions: (i) a peptide composed of the two common catalytic domains of HAS in the cytoplasmic region and the sequence including a part of the transmembrane region (rhHAS2-(122-414)), (ii) a peptide containing only two catalytic sites (rhHAS2-(122-355)), and (iii) a small peptide lacking one of the catalytic sites (rhHAS2-(122-347)) as illustrated in Fig.…”
Section: Production Of Rhhas2 Fusion Proteins In E Coli-it Has Beenmentioning
confidence: 99%